Soil Class Effects on the Optimum Design of Spatial Steel Frames Using the Dandelion Optimizer - Ugur, Ibrahim Behram; Kizilay, Ozkan (Mdpi, 2025)
In recent years, metaheuristic optimization methods have been widely applied across various engineering disciplines, offering effective solutions to complex problems that require both efficiency and reliability. Within this context, this study has two primary objectives. The first is to apply the Dandelion Optimizer (DO), inspired by the three-stage flight of dandelion seeds, to the optimum design of spatial steel frames and to evaluate its performance as a structural optimization algorithm. The second is to investigate the influence of different soil types, as defined in the Turkish Building Earthquake Code (TBEC-2018), on the optimum design outcomes. For this purpose, three benchmark spatial steel frames consisting of 132, 428, and 720 members were optimized using DO. The algorithm was implemented in MATLAB R2017b and integrated with SAP2000 v19 via the Open Application Programming Interface (OAPI). The design process was performed in accordance with TBEC-2018 and the AISC-LRFD, with strength, stability, and serviceability constraints considered. The results indicate that deteriorating soil conditions from ZA to ZE lead to substantial increases in structural demands. In the three analyzed models, total weight increases within the range of 45-57%, whereas total seismic base shear shows a much sharper rise, ranging from 160% to 292% These findings demonstrate both the practical applicability of the DO in steel frame optimization and the critical impact of soil conditions on structural design, underlining the importance of incorporating geotechnical factors into optimization frameworks.
Keywords: TBEC-2018; soil class; dandelion optimizer; space steel frame; optimal design